To add the two mixed numbers \(-1 \frac{1}{3}\) and \(-4 \frac{2}{3}\), we'll follow these steps:
- Convert each mixed number to an improper fraction.
\(-1 \frac{1}{3}\):
- Multiply the whole number part by the denominator: \(1 \times 3 = 3\).
- Add the numerator: \(3 + 1 = 4\).
- Since it's negative, we have \(-\frac{4}{3}\).
\(-4 \frac{2}{3}\):
- Multiply the whole number part by the denominator: \(4 \times 3 = 12\).
- Add the numerator: \(12 + 2 = 14\).
- Since it's negative, we have \(-\frac{14}{3}\).
-
Now add the improper fractions: \[ -\frac{4}{3} + (-\frac{14}{3}) = -\frac{4 + 14}{3} = -\frac{18}{3} \]
-
Simplify the result: \[ -\frac{18}{3} = -6 \]
Therefore, \(-1 \frac{1}{3} + (-4 \frac{2}{3}) = -6\).